Diagnóstico Cefalométrico em Relação Cêntrica. Uma Questão Académica? - Maria João Ponces (1999)
The controversy created around the influence of the condylar position on the diagnosis and planning of the orthodontical treatment was the reason for this study. Some authors highly defend the usage of articulator montage to perform the orthodontical study in centric relation. Accordingly to them, the study will not be considered valid if this is not the used technique. The formulated problem turns around the statistical meaning of the cefalometric diagnosis in centric relation and, as a consequence, on the practical clinical interest of such attitude. So, we tried to evaluate the meaning of this procedure, which can turn into a change on the diagnosis and planning of the treatment to implement in a certain number of cases. That way, centric slides were studied from a sample of 104 patients, who were received on first orthodontic consultation. The cases presenting values of centric slide equal or bigger than 1.8 mm were selected and, on a later phase, the measures obtained on the cefalometric trace of the radiographs taken in a profile incidence in maximum intercuspation were compared after converting the trace to centric relation. The comparison of the analytical average resulting from the achieved values, for each of the two types of analysis, aimed to certify the existence of a statistical meaning in 11 of 12 of the factors selected for evaluation. In nine of them was possible to detect a high statistical meaning. So, the extreme importance in adopting such attitude towards the cases presenting a centric slide equal or bigger than 1.8 mm seems to be confirmed. These cases were spotted in almost one third of the considered sample (30.8%), which looks like a significant frequency. Once we can not associate premonitory clinical signs to the existence of a significant centric slide, it can be concluded that the articulator mounting and the centric slide study should be a part of the orthodontical study. The results obtained from this study suggest that, in order to carry out a precise orthodontical diagnosis, the mandible position in centric relation should be considered instead of the traditionally accepted position of centric occlusion, associated to maximum intercuspation.